Feeding Preferences Of Bawean Deer (Axis Kuhlii Temminck, 1836) In The Ex-Situ Conservation Area Bali Zoo Park, Gianyar, Bali - Adyastari Dewi, Ni Kadek Thisya; Ginantra, I Ketut; Yuni, Luh Putu Eswaryanti Kusuma (Metamorfosa: Journal of Biological Sciences; Vol 10 No 2 (2023)DO - 10.24843/metamorfosa.2023.v10.i02.p08, 2023)
Bawean deer ( Axis kuhlii ) is endemic species of Bawean Island whose had a critically endangered status. This study aims to determine the feeding preferences of Bawean deer in the ex-situ conservation area ??Bali Zoo Park. This research was conducted from 6 January to 20 March 2020. Cafeteria feeding method was used to determine feeding preferences and continued with nutritional content test, namely crude protein (%), energy (kcal/g), kalsium (%) and phosphorus (%). Feeding preference was determined based on the Ivlev selection index. The feeding preference from the selection index (IS) showed local grass and sweet potato ( Ipomoea batatas ) was the preferred category, wheat bran ( Pollard ) was the proportional, elephant grass ( Pennisetum purpureum ) and carrots ( Daucus carota ) were the less preferred category. The nutritional content of Bawean deer had met their needs, in which crude protein ranges from 3.89 to 17.30%, energy ranges from 2.8585 to 3.6253 kcal/g, calcium ranges from 0.13 to 0.70% and phosphorus ranges from 0.10 to 0.84%.